2016
DOI: 10.1186/s40543-016-0105-6
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterization of transdermal patches for controlled delivery of duloxetine hydrochloride

Abstract: Background: Duloxetine hydrochloride is an antidepressant drug also approved for diabetic neuropathy, anxiety disorders, and fibromyalgia requiring repeated administration on chronic basis. The objective of this study was to develop a transdermal drug delivery system for duloxetine hydrochloride as a once daily dosage form. Methods: Transdermal patches were prepared by solvent evaporation method employing controlled release grades of HPMC in presence or absence of plasticizer PEG-400. FTIR and Differential sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 13 publications
2
43
0
1
Order By: Relevance
“…Furthermore, the film forming gel through DDDS provides better release of drugs in a controlled manner over a longer period of time in comparison to conventional methods of topical delivery ( Ahmed and Khalid, 2014 ). Ideally, a drug having non-ionic behaviour with molecular weight (M w ) less than 600 Da, log P value in the range of 1–4, solubility in both oils and water and low melting point (< 220 °C) penetrates the skin effortlessly ( Singh and Bali, 2016 ). Evidences suggest that duloxetine hydrochloride possesses acceptable physicochemical and biopharmaceutical assets in terms of molecular weight (333.9 g/mol), log P (3.84), aqueous solubility (5 mg/mL) and melting point (162−162 °C) ( Singh and Bali, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the film forming gel through DDDS provides better release of drugs in a controlled manner over a longer period of time in comparison to conventional methods of topical delivery ( Ahmed and Khalid, 2014 ). Ideally, a drug having non-ionic behaviour with molecular weight (M w ) less than 600 Da, log P value in the range of 1–4, solubility in both oils and water and low melting point (< 220 °C) penetrates the skin effortlessly ( Singh and Bali, 2016 ). Evidences suggest that duloxetine hydrochloride possesses acceptable physicochemical and biopharmaceutical assets in terms of molecular weight (333.9 g/mol), log P (3.84), aqueous solubility (5 mg/mL) and melting point (162−162 °C) ( Singh and Bali, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, a drug having non-ionic behaviour with molecular weight (M w ) less than 600 Da, log P value in the range of 1–4, solubility in both oils and water and low melting point (< 220 °C) penetrates the skin effortlessly ( Singh and Bali, 2016 ). Evidences suggest that duloxetine hydrochloride possesses acceptable physicochemical and biopharmaceutical assets in terms of molecular weight (333.9 g/mol), log P (3.84), aqueous solubility (5 mg/mL) and melting point (162−162 °C) ( Singh and Bali, 2016 ). Henceforth, in this study, film forming polymer-based duloxetine hydrochloride gel has been designed to fabricate.…”
Section: Introductionmentioning
confidence: 99%
“…A transdermal patch is cut into three longitudinal strips: one from the right side, one from the left side, and one from the center. The length of each strip is measured (90). The following equation is used for flatness determination:…”
Section: Flatness Testmentioning
confidence: 99%
“…Some surface-active agents have been shown to affect tight junction permeability 8 . Previous studies have shown that mixtures of hydrophilic polymers and cassava starch can form suitable film-formers for improved transdermal drug delivery 9 and HPMC have been effectively used to formulate transdermal films of low dose drugs 9,10 .…”
Section: Ex Vivo Permeation Studiesmentioning
confidence: 99%